High-Frequency Stimulation on Skeletal Muscle Maintenance in Female Cachectic Mice - Sato, Shuichi (Med Sci Sports Exerc, 2019)
Cancer cachexia, unintentional body weight loss due to cancer, affects patients’ survival, quality of life, and the response to chemotherapy. While exercise training is a promising intervention to prevent and treat cancer cachexia, our mechanistic understanding of cachexia’s effect on contraction-induced muscle adaptation has been limited to the examination of male mice. Since sex can impact muscle regeneration and the response to contraction in humans and mice, the impact of cachexia on the female response to eccentric contraction warrants further investigation. PURPOSE: The purpose of this study was to determine if high frequency electric stimulation (HFES) could attenuate muscle mass loss during the progression of cancer cachexia in female tumor bearing mice. METHODS: 16~18-week female wild-type (WT) and Apc(Min/+) (Min) mice performed either repeated bouts or a single bout of HFES (10 sets of 6 repetitions, ~ 22 minutes), which eccentrically contracts the Tibialis Anterior (TA) muscle. TA myofiber size, oxidative capacity, anabolic signaling and catabolic signaling were examined. RESULTS: Min had reduced TA muscle mass and IIa and IIb fiber size compared to WT. HFES increased muscle weight and the mean cross-sectional area of type IIa and IIb fibers in WT and Min mice. HFES increased mTOR signaling, myofibrillar protein synthesis, and attenuated cachexia-induced AMPK activity. HFES attenuated the cachexia-associated decrease in skeletal muscle oxidative capacity. CONCLUSION: HFES in female mice can activate muscle protein synthesis through mTOR signaling and repeated bouts of contraction can attenuate cancer-induced muscle mass loss.